Cover, Content, and Editorial Note from Borneo J Pharm Vol. 6 No. 2 May 2023 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2023)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm) was published in May 2023. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, and Management Pharmacy. This edition includes writings from five countries: Indonesia, Nigeria, the Philippines, Taiwan, and the United States. The authors come from several institutions, including Universitas Ahmad Dahlan, Universitas Muhammadiyah Mataram, University of California, Los Angeles, National Research and Innovation Agency Republic of Indonesia, Universitas Muhammadiyah Prof. Dr. HAMKA, Universitas Muhammadiyah Kalimantan Timur, Universitas Gadjah Mada, Universitas Sembilanbelas November Kolaka, Universitas Halu Oleo, Universitas Lambung Mangkurat, Universitas Jenderal Achmad Yani, Ahmadu Bello University, Institut Kesehatan Helvetia, Taipei Medical University, Sekolah Tinggi Ilmu Farmasi Riau, University of the Philippines Manila, and Universitas Diponegoro. Editorial boards are fully aware that there is still room for improvement in this edition; hence with all humility, willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope all parties, especially the contributors, can re-participate for publication in the next edition on August 2023. Wassalamu’alaikum Wr. Wb.